2016
DOI: 10.1186/s12893-016-0150-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, causes and management outcome of intestinal obstruction in Adama Hospital, Ethiopia

Abstract: BackgroundIn Africa, acute intestinal obstruction accounts for a great proportion of morbidity and mortality. Ethiopia is one of the countries where intestinal obstruction is a major cause of morbidity and mortality. This study aims to determine prevalence, causes and management outcome of intestinal obstruction in Adama Hospital in Oromia region, Ethiopia.MethodA hospital based cross-sectional study design was used. Data covering the past three years were collected from hospital medical records of sampled pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
87
6
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(131 citation statements)
references
References 7 publications
32
87
6
6
Order By: Relevance
“…A study conducted by Soressa U et al concluded that patients who presented within 24 h of symptom presentation are less likely to develop an unfavourable outcome, compared with patients who presented after 24h. 9 Similarly, a study conducted by Heis HA et al showed that delayed presentation and/or surgical intervention frequently results in relatively poor surgical outcomes and/or longer hospital stays.…”
Section: 10mentioning
confidence: 99%
“…A study conducted by Soressa U et al concluded that patients who presented within 24 h of symptom presentation are less likely to develop an unfavourable outcome, compared with patients who presented after 24h. 9 Similarly, a study conducted by Heis HA et al showed that delayed presentation and/or surgical intervention frequently results in relatively poor surgical outcomes and/or longer hospital stays.…”
Section: 10mentioning
confidence: 99%
“…[3,11] In the last 50 years, the incidence of strangulated hernia has decreased from 55.8% to 26.5%, while tumors increased from 6.3% to 22.2% and adhesions remained statistically unchanged. [8] Volvulus and intussusception were reported to be the most common causes of AMBO in Ethiopia, [12] and hernia remained the most common cause of intestinal obstruction in Sudan in some research. [13] The etiology of AMBO has varied over time and according to geographic region in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel resection and anastomosis was the commonest intra-operative procedure done and is associated with postoperative complications [15]. Over the last century there have not been significant changes in the anatomical location of obstruction.…”
Section: Discussionmentioning
confidence: 99%